Study the Attenuation Ability of γ-Rays Emitted from Co-60 Radioactive Isotope in PES/CaFe2O4 Composite Shields (Journal of the College of Basic Education, 2022)
In this present study, nuclear composite shields were prepared from polyester (PES) as a matrix material and reinforcement it with a ferrite spinel powder (CaFe2O4) prepared with three different sintering temperatures (800, 1000, and 1200Co) by the ceramic method to obtain a different granular size powder. Attenuation parameters of γ-rays emitted from the Co-60 radioactive isotope were studied using GM counter tube for six types of shields. The first type was PES pure shield, and the others were composite shields consist two types of PES reinforced by 15% concentration of reinforced powder prepared with different sintering temperature degrees (800, 1000Co), and three types with different concentrations (2%, 7% and 15%) of reinforced powder prepared with sintering temperature degree of 1200Co. The results showed that the transmission factor (TF) value decreased with increasing of the sintering temperature degree of reinforcement powder and its concentration in composite shields, and increased with increasing of the thickness of the shield. Also, the linear attenuation coefficient (μ) calculations showed increasing its value with increasing of concentration and sintering temperature degree of reinforced powder. In addition, It was observed that when both of the concentration and its sintering temperature degree of reinforced powder were increased, the values of half value layer (HVL), the tenth value layer (TVL), and the mean free bath (λ) were decreasing. These results show that the PES/15%CaFe2O4 that prepared at 1200Co was the best shield because it achieved a higher value of μ and lowest values of HVL, TVL and λ compared to the other shields.